Livestock feed markets across agro-ecological zones of Burkina Faso: Feed provenance, price and quality - Ayantunde, Augustine A.; Amole, Tunde A.; Duncan, Alan J. (Frontiers Media, 2023)
Livestock form a major means of livelihood in Burkina Faso where almost 80% of the rural population keep sheep and goats. However, the major constraint to livestock productivity is seasonal feed scarcity. To bridge the increasing feed gap, particularly in the dry season, livestock keepers are increasingly turning to purchase of feeds from markets, which has led to emergence of feed markets in peri-urban towns and cities in the Sahel. To characterize the dynamics of these livestock feed markets, to inform and guide the development of efficient feeding systems in peri-urban livestock production, we conducted surveys in feed markets in four major towns and cities of Burkina Faso across all the agro-ecological zones. Results from this study showed that the feed types on sale included browse, bush hay, bran of maize, millet, sorghum, rice and wheat, legume residues, cereal straw and agro-industrial by-products such as cottonseed cake and concentrate feed for ruminants. The average number of feeds sold per vendor ranged from 1.5 ± 0.1 in early dry season to 3.5 ± 0.4 in late dry season. More than 80% of the feed sellers in each location reported that generation of additional income for the household was the principal reason for feed sale. The price of livestock feeds sold at different locations in Burkina Faso varied significantly with season, market location and feed type. Cottonseed cake had the highest crude protein content in all locations and across seasons ranging from an average of 16.3 to 31.9% while cereal straw (millet, maize and sorghum straw) had the lowest crude protein content of 3.5%. The results also showed a lack of a clear trend in terms of relationship between price and nutritional quality which confirms the absence of quality standardization for feeds on sale in our study sites. In developing feed industry in the region, the issue of quality standardization needs to be addressed to facilitate establishment of nutritive value-based pricing and to ensure that consumers pay a premium for quality products.